Modern Directions of Creating New Protective Materials and Tissues for Means of Individual and Collective Protection against Toxic Chemicals and Pathogenic Microorganisms - V. V. Zavialov; S. V. Kujelko; N. V. Zavialova; V. A. Kovtun; V. I. Kholstov; Yu. F. Taranchenko; L. M. Slastilova; E. N. Efremenko; A. P. Sin’keliov (Вестник войск РХБ защиты)
The purpose of this work is to identify technologies of the production of materials and fabrics that provide protection against toxic chemicals and pathogens for the development of personal and collective protective equipment. These materials and tissues should have specific properties of «self-cleaning» (selfdegassing). The article is dedicated to the consideration of the results of the use of new protective materials and fabrics during the creation of modern filtering and sorbing protective equipment of the «soldier of the future». It is shown in the article, that regardless of the method of producing protective materials on the basis of activated carbon or sorbents, they do not possess the «self-cleaning» properties. Their common significant drawback is the possibility of desorption of toxic substances. In addition, there is also a limitation of their protective properties by the sorption capacity of activated carbon (carbon fibers). As a result, the absence of toxic vapors behind the layer of protective material can be guaranteed for a limited period of time. As a rule, this period of time does not exceed 24. In the nearest future the electrospinning technology, used to obtain filtering fabrics, will create a wide range of materials with various properties, including anti-aerosol, degassing, antimicrobial, etc. The metal organic frameworks (MOFs) based on zirconium, NU-1000, UiO-66, seem to be the most attractive among the MOFs for the creation of means of degassing and indication of toxic agents. The analysis of data obtained in the field of creation of filtering and sorbing «self-cleaning» (self-degassing) materials for personal protective equipment showed that these materials can acquire such properties due to their functionalization while using nanosized metalcontaining particles with antibacterial properties, as well as enzymes that catalyze hydrolysis of certain highly toxic compounds and their degradation products.